(untitled) (Nexo Revista Científica, 2021)
A method has been presented for the direct determination of shear force in oblique cross-sections of reinforced concrete structures using a classic formula Q=bzτ, when the main problems of determining the shear force in oblique cross-sections are related to finding cleaving stresses in concrete and the shape of a stress-block of normal stresses in the design section, with no principles of practical division between the forms of failure in oblique sections due to concrete compression or shear. This work incorporates a criterion for dividing the forms of failure due to concrete compression or shear, based on the assumed shape of a compression stress-block with a segment cut away in a normal section, passing through the top of an inclined crack. The height of the compressed area in this normal section is defined from simultaneous solution of the equations of equilibrium in the moments in normal and oblique sections, from testing the experimental beams made of concrete and gas-concrete. This work deals with seeking the approaches for solving the above-mentioned problems in practice. The data of testing beams from gas-concrete and heavy-weight concrete have been used. Strain gauges were used to measure concrete and reinforcement deformities, computer processed thereafter. The studies have been considered on determination of cleaving stresses in oblique sections, further verified according to this method on certain alternative schemes of their application. A practical method for finding the shear force depending on the value of a shear span has been proposed. The work can encourage active discussion of this computation method.